2011
DOI: 10.1039/c1jm12402a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of thianthrene-based poly(phenylene sulfide)s with high refractive index over 1.8

Abstract: Highly refractive thianthrene-based poly(phenylene sulfide)s (TPPSs) have been developed. The TPPSs were prepared from 2,7-difluorothianthrene and dithiols, including 4,4 0 -thiobisbenzenethiol (TBBT), m-benzenedithiol (mBDT), or sodium sulfide nonahydrate based on aromatic nucleophilic substitution reactions, and showed excellent thermal stabilities such as relatively high glass transition temperatures in the range of 143-147 C and 5% weight-loss temperatures over 430 C. All of the TPPSs exhibited very high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…The introduction of substituents with a high molar refraction and a small molar volume, such as aromatic rings, halogen atoms except fluorine, sulfur atoms, and metal atoms, efficiently increases the refractive index of the polymers . To date, a variety of high refractive index and highly transparent polymers have been developed by the efficient incorporation of the above components, particularly sulfur atoms and aromatic rings; several examples have accomplished a high refractive index value of over 1.7 . Recently, the processability of high refractive index polymers has been paid much attentions as well as the performance (e.g., high refractive index, high transparency, and high thermal stability) because nano‐ and microfabrication of high refractive index polymers is absolutely necessary for the miniaturization of the opto‐integrated assembly process and devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of substituents with a high molar refraction and a small molar volume, such as aromatic rings, halogen atoms except fluorine, sulfur atoms, and metal atoms, efficiently increases the refractive index of the polymers . To date, a variety of high refractive index and highly transparent polymers have been developed by the efficient incorporation of the above components, particularly sulfur atoms and aromatic rings; several examples have accomplished a high refractive index value of over 1.7 . Recently, the processability of high refractive index polymers has been paid much attentions as well as the performance (e.g., high refractive index, high transparency, and high thermal stability) because nano‐ and microfabrication of high refractive index polymers is absolutely necessary for the miniaturization of the opto‐integrated assembly process and devices.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] To date, a variety of high refractive index and highly transparent polymers have been developed by the efficient incorporation of the above components, particularly sulfur atoms and aromatic rings; several examples have accomplished a high refractive index value of over 1.7. [7][8][9][10] Recently, the processability of high refractive index polymers has been paid much attentions as well as the performance (e.g., high refractive index, high transparency, and high thermal stability) because nano-and microfabrication of high refractive index polymers is absolutely necessary for the miniaturization of the opto-integrated assembly process and devices. Injection molding is commonly used for the fabrication of high refractive index and highly transparent polymers; however, it is not suitable for nanoand microfabrication.…”
mentioning
confidence: 99%
“…It was demonstrated that the final products can work as a highly efficient active layer as an electrolyte in the lithium battery. Especially, an introduction of sulfur element into the polymer structure is one of the valid strategies for developing high‐refractive index plastics with a high Abbe number, while there are very few examples to demonstrate the optical materials made directly by sulfur (S 8 ) as a starting material. Hence, the development of new application manners with sulfur is of significance especially in the industrial fields in terms of the effective utilization of limited resources.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, an introduction of sulfur element into the polymer structure is one of the valid strategies Additional Supporting Information may be found in the online version of this article. for developing high-refractive index plastics 13 with a high Abbe number, [14][15][16][17][18][19] while there are very few examples to demonstrate the optical materials made directly by sulfur (S 8 ) as a starting material. Hence, the development of new application manners with sulfur is of significance especially in the industrial fields in terms of the effective utilization of limited resources.…”
mentioning
confidence: 99%
See 1 more Smart Citation